Reimagining VAWA: Why Criminalization Is a Failed Policy and What a Non-Carceral VAWA Could Look Like - Goodmark, Leigh (Violence against women, 2021)
The Violence Against Women Act (VAWA) is the signature federal legislative accomplishment of the anti-violence movement and has ensured that criminalization is the primary response to intimate partner violence in the United States. But at the time of its passage, some anti-violence activists, particularly women of color, warned that criminalization would be problematic for a number of reasons, a caution that has borne fruit in the 25 years since VAWA’s passage. This article critiques the effectiveness of criminalization as anti-domestic violence policy and imagines what a non-carceral VAWA could look like.